Design and implementation of web-based open access rapeseed-mustard disease bibliographic information system (Journal of Oilseed Brassica, 2026)
The advancement of research in the field of rapeseed-mustard diseases is clear to everyone. The numbers of articles are being published each year, resulting in increase of knowledge at every moment. Problem identification, future planning, implementation, and interpretation of individual research studies all depend on ready access to all of the relevant existing rapeseed-mustard diseases research knowledge. We implemented web-based bibliography information system (RMBiblio), offer researchers easy and fast access of references in the field of rapeseed-mustard disease research. Metadata formats suitable for describing scientific publications have been used in creating the database. System supports a wide range of publication types, and has features like advanced search option, extraction of publications statistics based on a variety of visual form based queries, etc. These sophisticated and versatile searching facilities have been implemented using full text search options, the rows returned are automatically sorted with the highest relevance first. HTML, CSS, was used for development of user interface; PHP is the middleware and MySql for the backend.